(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rumengan AP, Mandiangan ES, Tanod WA, Paransa DSJ, Paruntu CP, Mantiri DMH. 2021. Identification of pigment profiles and antioxidant activity of Rhizophora mucronata mangrove leaves origin Lembeh, North Sulawesi, Indonesia. Biodiversitas 22: 2805-2816. Mangroves plants contain unique pigments which can serve both nutraceutical and pharmaceutical purpose. Therefore, this preliminary study aims to identify the pigment profiles of Rhizophora mucronata mangrove leaves (HPLC method) and to computationally evaluate the antioxidant mechanism of the pigments (PASS and STITCH analysis). Furthermore, it evaluated the antioxidant capacity of R. mucronata leaves extracts (DPPH method), and the pigment profiles detected using HPLC were chlorophyll a (68.61%), chlorophyll b (27.69%), lutein (29.94%), beta-carotene (14.05%), pheophytin a (8.72), violaxanthin (5.19%), and neoxanthin (3.65%). Beta-carotene, lutein, neoxanthin, and violaxanthin were predicted to have potential as antioxidants properties using PASS analysis. While neoxanthin and violaxanthin were predicted as free radical scavengers, beta-carotene was an Nrf-2 stimulant. The STITCH analysis showed that the pigments contained in the leaves interacted synergistically by activating as antioxidant enzymes and inhibiting the expression of oxidative stress proteins. The ethanol extract of R. mucronata leaves may be a potent antioxidant with an IC50 20.99 ± 0.33 µg/mL. Therefore, the pigment contained in R. mucronata leaves is a potential source of antioxidants.